Reexamining the Credibility of the Joseph Schacht Concept of Sanad Hadith: Menguji Kembali Kredibilitas Konsep Joseph Schacht terhadap Sanad Hadis - Ahmad Ubaidillah Ma'sum Al Anwari; Muhammad Iqbal Trenggono; Muhammad Fahrul Asyahudi (Jurnal Living Hadis, 2023)
Joseph Schacht, through the book The Muhammadan Jurisprudence, raises a criticism of sanad which considers that hadith did not start from the Prophet, but from tabi'in. It's just that Schacht's concept is considered weak because he is inconsistent and forgets a lot of data and important aspects in the study of hadith. This article appears as the author's attempt to explain the concepts promoted by Schacht and also some of the problems carried out by Schacht. With the help of the descriptive-analytical method combined with a comparison of experts' arguments as a medium of analysis, it can be seen how gaps emerge in Schacht's attitude. The results of the analysis explain that the Schacht controversy is related to; first, Schacht's rejection of the hadith which is not in line with the data of the companions which are part of the hadith; secondly, the theory built by Schacht can be said to be very weak, because much of the data found refutes Schacht's hypothesis; third, there is subjectivity in the use of data and analysis results; and fourth, Schacht, who is known as an expert in Islamic law, should study hadith, but he does not believe that hadith comes from the Prophet.